Application of combination therapy for treating glioblastoma - Xu, Xuanqi (Transactions on Materials, Biotechnology and Life Sciences, 2024)
Glioblastoma (GBM), an aggressive brain tumor with a high mortality rate, is also extremely easy to differentiate and metastasize, making it one of the most dangerous cancers in the world. The aim of this research was to establish a unique combination therapy that combines surgery and vaccination to treat GBM. This research uses predictive clinical trials and artificial intelligence analytics to summarize and examine the side effects and remedies of combination therapy, thus ensuring the physical and mental health of patients and aiming to create a low-cost treatment with a high success rate. Since angiogenesis is the most challenging side effect to treat, other remedies for this symptom were also summarized in this research. This means that this combination therapy may provide better success rates and a more patient-appropriate course of care compared to earlier approaches. It is hoped that in the coming time, this combination treatment plan will be adopted and implemented, and it is hoped that more efficient treatment methods will be proposed so that all GBM patients can be cured.